Analysis of pressure drop and blast pressure leakage of passive air blast safety valves: An experimental and numerical study. (February 2022) - Brenner, Lorenz; Jenni, Christian; Guyer, Flurin; Stähli, Patrick; Eberlein, Robert; Huber, Matthias; Zahnd, André; Schneider, Martin; Tillenkamp, Frank
Abstract: The purpose of passive air blast safety valves is to protect people and technical installations in buildings or facilities. In case of explosions, e.g. due to technical failures in an oil- and gas refinery, the safety valve should close in milliseconds with the incident shock wave and substantially reduce the blast-pressure leakage into the building. On the other hand, the safety valve should exhibit a low pressure drop in normal operation in order to reduce the power consumption of the ventilators. One main difficulty in the design of such safety valves is to meet the minimum technical requirements, while ensuring the functionality in intrinsically different operating modes. Therefore, the present study proposes a target-oriented evaluation and optimization procedure for such devices, incorporating comprehensive numerical and experimental investigations. CFD, FEM and FSI analyses are regarded as an appropriate approach to predict valve performance parameters and to gain additional insights into the flow or structural behavior of the safety valve, which serves then as a basis for geometrical optimizations. The introduced procedure is exemplified on an existing passive air blast safety valve as a case study. The performance of the new design is significantly increased in ventilation operation, while meeting the performance criteria in the stress case when subjected to blast loads. Highlights: An optimization procedure for passive air blast safety valves is presented. The procedure is exemplified on an existing safety valve as a case study. Numerical and experimental analyses deliver insights for geometrical optimizations. The safety valve performance is significantly enhanced in ventilation operation.